PENDAMPINGAN DAN PELATIHAN PENGUATAN COMPUTATIONAL THINKING SEBAGAI KEMAMPUAN UTAMA ABAD 21 - Antonius Rachmat Chrismanto; Katon Wijana; Eko Verianto; Argo Wibowo; Yuan Lukito (Universitas Sanata Dharma, 2020)
The skills needed in the 21st century are communication, collaborative, creativity innovation, and, critical thinking problem solving. One that is closely related to mindset is critical thinking problem solving. Critical thinking and being able to solve problems means the ability to understand a complex problem, connect information to other information, and finally find the solutions of the problem. This ability is closely related to the field of Information Technology (IT) because this field really needs a structured, coherent mindset, analysis, and computational thinking. This ability is very much needed by the young generation of Indonesia today.The Information Technology of UKDW Faculty (FTI)’s partner, Bopkri I Yogyakarta High School, has the same vision to prepare students to have real and applicable abilities. Students need regular and structured training to achieve these goals. Bopkri I and FTI work together in the form of community service training in strengthening computational thinking by implementing basic programming, advanced programming, and training evaluation.This program was held in 2 major stages., The first stage consists of strengthening computational thinking using basic programming training in general, and the second using advanced programming training in the form of competitive programming and its simulations. Students were given complete material, face-to-face/online knowledge transfer, complete modules, exercises, and direct simulations by some experienced lecturers from FTI UKDW.